Genetic analysis of porcine circovirus type 2 (PCV2) in Queensland, Australia. Issue 8 (22nd May 2020) - Mone, NK; Clark, NJ; Kyaw‐Tanner, M; Turni, C; Barnes, TS; Parke, CR; Alawneh, JA; Blackall, PJ; Meers, J
Abstract : Objective: To determine the current porcine circovirus type 2 (PCV2) genotypes circulating in pigs in Queensland (QLD). Methods: The PCV2 infection status of pigs was determined by real‐time PCR testing of 210 lymph nodes and 30 serum samples derived from 45 QLD farms. PCV2‐positive samples from 22 pigs from 15 farms were subjected to conventional polymerase chain reaction (PCR) and sequencing of the full PCV2 genome. Phylogenetic analysis of 17 of these sequences in relation to published PCV2 sequences was then performed, and the genotypes were compared. Results: PCV2 DNA was detected in 95 lymph nodes and 15 serum samples. Phylogenetic analysis of 17 PCV2 sequences demonstrated that seven belonged to genotype PCV2b, two to PCV2d, one to PCV2f and seven to an "intermediate group" that clustered with PCV2d on the full genome analysis. Conclusion: This work confirms earlier studies reporting the presence of PCV2b in Australia. It is the first study to report that PCV2d and PCV2f are also present in this country. PCV2d is currently a fast‐spreading genotype globally, with reported high virulence. The potential implications of these findings with respect to pathogenicity and vaccine efficacy require further investigation.